ПОШИРЕНІСТЬ ГРИЗУЧИХ КОМАХ-ФІЛОФАГІВ У ЛИСТЯНИХ НАСАДЖЕННЯХ м. ХАРКОВА - Sokolova, I. N.; Shvydenko, I. N.; Kardash, E. S. (public organization "Ukrainian Entomological Society", I.I. Schmalhausen Institute of Zoology of National Academy of Sciences of Ukraine, Institute of Plant Protection of National Academy of Agrarian Sciences of Ukraine, 2020)
The aim of research was to reveal the features of the prevalence of dendrobiont phylophagous insects with gnawing mouthparts in deciduous stands of streets, parks and Forest park of the city of Kharkiv. Researches were carried out in 2017–2020 by foliage inspection and insects collecting each 1–2 weeks of vegetative season from Acer, Aesculus, Alnus, Betula, Fraxinus, Populus, Quercus, Robinia, Salix, Sorbus, Tilia, and Ulmus. The prevalence of certain species of phyllophages was assessed by manual collection, using an entomological net, collection of larvae with rearing on the leaves of forage tree, as well as by characteristic damage (particularly miners). In the street, park and forest-park stands of Kharkiv, 108 species of phyllophagous insects with a gnawing mouthparts were found and conditionally divided into groups in accordance with the feeding habits and taxonomy: insects with an open lifestyle (61 species) from the orders Hymenoptera (2 species) and Lepidoptera (59 species); insects with an open lifestyle from the order Coleoptera (33 species); insects with a hidden lifestyle (miners) (14 species) from the orders Coleoptera (2 species) and Lepidoptera (12 species). In the forest park, 105 species (97.2%) of phyllophagous insects with gnawing mouthparts were found, in parks - 67 species (62%), in street stands - 33 species (30.6 %). Menchinick’s index (DMn) values for chewing phyllophagous insects were evaluated as 10.2; 8.2, and 5.7 in forest park, parks, and streets. Jaccard’s index (Cj) values were evaluated when comparing different types of urban stands in Kharkiv. The greatest similarity of the complexes of phyllophagous insects was found in parks and forest park (Cj=0.52 for Coleoptera with open lifestyle; Cj =0.59 for Lepidoptera and Hymenoptera with open lifestyle and Cj=1 for leaf-miners from Coleoptera and Lepidoptera). Most of the revealed species were single or rare. Xanthogaleruca luteola was a common species in the streets, parks and Forest park, Chrysomela populi, and two Clytra species in the Forest park, Tomostethus nigritus in parks, Cameraria ohridella in the street and park stands. Plagiora versicora and Crepidodera aurata were found only in street stands.